Pelaksanaan Hubungan Kerja Manajemen dengan Serikat Pekerja pada PT. Arara Abadi di Perawang Kecamatan Tualang Kabupaten Siak Sri Indrapura - Pratama, Anggi; Herianto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The research was conducted on PT. Arara Abadi Perawang. The purpose of thisstudy is to know the implementation of management employment relationship with laborunion at PT. Arara Abadi because good employment relationship is harmony relations inindustrial relationship.This research is a descriptive study with qualitative approach. Where there are160 samples. The data used is primary data and secondary data. The primary dataobtained from questionnaire had given to permanent employees who joined in MitraAbadi Riau labor union on PT. Arara Abadi and interview with management andadministration staff. The secondary data obtained from SOP and other documents needed.From the analysis conducted known that the implementation of managementemployment relationship with labor union due management want to create harmonyrelations and good industrial relationship. And from the analysis conducted also knownthat implementation of employment relationship with labor union is very good overall.But the biggest problem is less responsive from management in seeing problems andcomplains from employess and unforceful management in giving punishment.Keywords: implementation, employment relationship, management, labor union.